Betacyanins obtained from alternative novel sources as natural food colorant additives: incorporated in savory and sweet food products - Roriz, Custódio Lobo (2018)
The aim of this study was to assess the performance and stability of betacyanin compounds present in enriched extracts of red-fleshed pitaya peels (Hylocereus costaricensis) and the flowers of Amaranthus caudatus; they were evaluated as natural food colorants in tagliatelle pasta and meringue cookies. The recovered natural extracts showed promising stability, maintaining a deep pink color over a storage time of 14 days, without deeply changing the chemical composition. A number of factors were assessed, including the microbial load, texture, color, nutritional value, and contents of organic acids, fatty acids, and even free sugars of the products. Some significant interactions between the type of colorant and storage time contributed to the changes in some analyzed parameters, as can be observed from the results for organic and fatty acids in the tagliatelle pasta and meringue cookies. Another significant achievement was the reduction in the microbial load during the storage time, which strengthens the antibacterial power of these natural extracts.